Determining the Optimal Injection Molding Process Parameters by Response Surface Methods - Rajalingam, Sokkalingam (8th CUTSE International Conference 2013, 2013)
The difficulty in adjusting optimum process parameters setting may cause defects on injected molded parts such as shrinkage. In this study the author wants to determine the optimal injection molding process parameters which will minimize the shrinkage defect on a plastic cell phone housing component. The machine process setting in use currently caused shrinkage where variation in the dimension of the length below the specification limits. Therefore the experiment is needed to identify the optimal process parameters that could be set to maintain the length dimension closest to the target value with smallest possible variation. The process parameters selected in this study are the mould temperature, injection pressure and screw rotation speed. The Response Surface Methods (RSM) was used to determine the optimal moulding process parameters. The significant factors affecting the responses were identified from ANOVA. Statistical results and analysis are used to provide better interpretation of the experiment.